KETERLIBATAN KERJA KARYAWAN, LOYALITAS KERJA DAN KERJASAMA TIM TERHADAP KINERJA KARYAWAN PT. AGRO WIRA LIGATSA PASAMAN BARAT - Wico Mardiono Putra; Zusmawati Zusmawati (Jurnal Bina Bangsa Ekonomika, 2024)
This research aims to examine the influence of Employee Job Involvement, Job Loyalty, and Team Cooperation on Employee Performance at PT. Agro Wira Ligatsa Pasaman Barat. The independent variables used in this study are Employee Job Involvement, Job Loyalty, and Team Cooperation. Meanwhile, the dependent variable in this research is Employee Performance. The determination of the research sample uses the Total Sampling method, and a sample of 112 employees is obtained. The results of the study show that there is a significant influence of employee job involvement on employee performance, thus accepting the first hypothesis. There is a significant influence of job loyalty on employee performance, thus accepting the second hypothesis. There is a significant influence of team cooperation on employee performance, thus accepting the third hypothesis